The Business of Software: The Cliché defense. - Armour, Phillip G. (Communications of the ACM, 2009)
In this article the author discusses the use of clichés by managers who work in the software development industry. A manager who uses clichés can sound focused but in reality avoid saying anything of substance, the author states. Techniques to defend against such managers are described including defending against the clichés "Do it right the first time" and "Work smarter, not harder."